Some Issues that are Causing the Trial to Be Delayed (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article explores the reasons for effective coping with the mechanisms by which the court delays the process, the development of a professional action plan in preparing the case for a hearing, as well as the reasons for the delay that the parties can use based on the actual circumstances of the case, and highlights specific aspects of speeding up proceedings.